2022
DOI: 10.1021/acsinfecdis.2c00071
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-Linked Cholesterol Incorporation in Rift Valley Fever Virus Particles Promotes Infectivity

Abstract: Viruses rely on an array of cellular metabolites to replicate and form progeny virions. One set of these molecules, polyamines, are small aliphatic molecules, which are abundant in most cells, that support virus infection; however, the precise roles of polyamines in virus infection remain incompletely understood. Recent work demonstrated that polyamine metabolism supports cellular cholesterol synthesis through translation of the key transcription factor SREBP2. Here, we show that the bunyavirus Rift Valley fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Polyamines are important for replication of various viruses. In recent years the Mounce group demonstrated that polyamines ensure infectivity of virions either by direct incorporation into the virus particle [55] or by incorporation of cholesterol [56] thus conferring binding of virions to the cell surface and concomitant virus entry [55,57,58]. During polyamine exhaustion, non-infectious viral particles can be formed, as shown for Bunyaviruses [59].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are important for replication of various viruses. In recent years the Mounce group demonstrated that polyamines ensure infectivity of virions either by direct incorporation into the virus particle [55] or by incorporation of cholesterol [56] thus conferring binding of virions to the cell surface and concomitant virus entry [55,57,58]. During polyamine exhaustion, non-infectious viral particles can be formed, as shown for Bunyaviruses [59].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are important for the replication of various viruses. In recent years, the Mounce group demonstrated that polyamines ensure the infectivity of virions either by direct incorporation into the virus particle [ 59 ] or by incorporation of cholesterol [ 60 ], thus conferring binding of virions to the cell surface and concomitant virus entry [ 59 , 61 , 62 ]. During polyamine exhaustion, non-infectious viral particles can be formed, as shown for Bunyaviruses [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibiting viral entry, translational arrest and autophagy are also considered integral components of host defense against RVFV ( 86 , 87 ). Cholesterol can be incorporated into RVFV particles and enhance RVFV infectivity in a polyamine-dependent manner ( 88 ). Studies have found that a high-cholesterol diet can lead to liver cholesterol accumulation, and it mainly affects cerebral vessels among the vascular effects, with up-regulation of LDLr and LRP1 detected in cerebral vessels ( 89 ).…”
Section: Conclusion and Prospectmentioning
confidence: 99%